ХАРАКТЕРИСТИКА ПРАВООТНОШЕНИЙ ПО УРЕГУЛИРОВАНИЮ КОЛЛЕКТИВНЫХ ТРУДОВЫХ СПОРОВ - Нуруллаева , Ойдин (Educational Research in Universal Sciences, 2023)
Labor disputes are disagreements between the employer and the employee, and other subjects of labor law on issues of remuneration, working conditions or certain clauses of the labor agreement, as well as the application of labor law norms, which were declared to the appropriate jurisdictional body.